Modelagem cinética da síntese de galacto-oligossacarídeos usando a β-galactosidase de Kluyveromyces lactis - Schultz, Guilhermina (2020)
Galacto-oligosaccharides (GOS) have a high commercial value and are used in the food industry. GOS are non-digestible oligosaccharides (NDO), which are considered prebiotics. They can be produced enzymatically from substrates rich in lactose (whey, whey permeate or lactose) using the enzyme β-galactosidase as a catalyst, through a kinetically controlled reaction characterized by competition between GOS synthesis reactions (transgalactosylation) and lactose hydrolysis. In these substrates there are considerable concentrations of cations (Na+, Mg+2, Ca+2 and K+) that can affect the activity of β-galactosidase. Thus, the objective of this work was to study the kinetics of the enzymatic synthesis of GOS using lactose and whey permeate as substrate, using the free enzyme β-galactosidase from Kluyveromyces lactis (Lactozym 3000 L HP G) as a catalyst, which has GRAS status, to arrive at mathematical models that allow the use of computational tools in order to optimize the process. To achieve this goal, several reactions were conducted. In the initial rate assays, most of the experiments were carried out on 220 g/L of lactose (pure, or present in whey permeate) and chloride salts were added when using pure lactose, to verify their influence on the initial rate of synthesis and hydrolysis, total activity and selectivity. The results obtained indicate that, within the studied region, sodium, among all the ions tested, was the one that caused the greatest selectivity. Calcium inhibited the initial rate of enzyme synthesis and hydrolysis. In media containing potassium together with sodium, the effect of sodium inhibition on the initial rate of hydrolysis was even more pronounced. A similar effect occurred when potassium and calcium were used, since the inhibition caused by calcium, in the total activity, initial rate of synthesis and hydrolysis seems to be potentiated by the presence of potassium. For the kinetic model, fit were made by non-linear regression, in which several initial concentrations of lactose and enzyme were used. The model has nine adjustable parameters and characterizes the formation of Glb, tri, tetrasaccharides and enzymatic inactivation. A bootstrap method, based on the residues obtained during the adjustment procedure, is employed to calculate the confidence intervals for the parameters. This model fits well with the experimental data. As a result, this model can be useful for optimization of bioreactors and process design, as well as process control.